2005
DOI: 10.1073/pnas.0503986102
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization of a mammalian membrane protein overexpressed in Saccharomyces cerevisiae

Abstract: The Ca 2؉ -ATPase SERCA1a (sarcoplasmic-endoplasmic reticulum Ca 2؉ -ATPase isoform 1a) from rabbit has been overexpressed in Saccharomyces cerevisiae. This membrane protein was purified by avidin agarose affinity chromatography based on natural biotinylation in the expression host, followed by HPLC gel filtration. Both the functional and structural properties of the overexpressed protein validate the method. Thus, calcium-dependent ATPase activity and calcium transport are essentially intact after reconstitut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
88
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(90 citation statements)
references
References 43 publications
2
88
0
Order By: Relevance
“…However, it has also been reported recently (7) that crystals of cytochrome b 6 f that diffract well can be obtained only by adding PL, which stabilize the intact complex. Successful crystallization of a heterologously expressed rabbit sarcoplasmic-endoplasmic reticulum Ca 2ϩ -ATPase isoform also requires addition of native PL (8). In addition, the amount of residual PL associated with the P i ͞glycerol-P antiporter GlpT is important for crystallization (9).…”
mentioning
confidence: 99%
“…However, it has also been reported recently (7) that crystals of cytochrome b 6 f that diffract well can be obtained only by adding PL, which stabilize the intact complex. Successful crystallization of a heterologously expressed rabbit sarcoplasmic-endoplasmic reticulum Ca 2ϩ -ATPase isoform also requires addition of native PL (8). In addition, the amount of residual PL associated with the P i ͞glycerol-P antiporter GlpT is important for crystallization (9).…”
mentioning
confidence: 99%
“…Although more structures of eukaryotic membrane proteins have been determined using material isolated from heterologous overexpression in the methylotrophic yeast Pichia pastoris, this difference is likely due to the popularity of P. pastoris because of its ability to produce a large biomass during fermentation with methanol 8 . However, recent work has demonstrated that S. cerevisiae is also a suitable host for obtaining enough material that will give high-resolution membrane protein structures 9,10 .…”
Section: Introductionmentioning
confidence: 99%
“…3). This type I packing is also observed for re-lipidated SERCA1a (Jidenko et al, 2005) and in general for ATPases solubilized from native tissue: SERCA1a (Toyoshima et al, 2000;Sørensen et al, 2004) and Na + ,K + -ATPase . The molecular-replacement solution was subjected to rigid-body and limited restrained refinement (R = 44.1% and R free = 47.4%).…”
Section: Structure Determination and Analysismentioning
confidence: 73%
“…LMCA1 eluted as a monomer in size-exclusion chromatography, similar to C 12 E 8 -solubilized SERCA1a from rabbit SR membranes (Andersen et al, 1986). Prior to crystallization, LMCA1 was re-lipidated with 1,2-dioleoyl-sn-glycero-3-phosphocholine (DOPC) as previously described for SERCA1a expressed in yeast (Jidenko et al, 2005). Excess lipid that was not solubilized by the detergent was removed by ultracentrigufation and LMCA1 was incubated with the Ca 2+ chelator EGTA and AlF 4 À to mimic the E2-P i -occluded form as a transition state in dephosphorylation.…”
Section: Purification and Crystallization Of Lmca1mentioning
confidence: 99%
See 1 more Smart Citation